Land Conflicts in Wadas: Perspectives from Islamic Law - Muna, Nailal; Faidati, Ashima (Sharia and Law Faculty, 2023)
The Wadas case refers to a dispute over land that has arisen between a local community and the government in Wadas Village, Bener District, Purworejo, Central Java, as a direct outcome of a large-scale construction project. Since 2018, when an environmental permit was given by the governor stating that Wadas was included in the location of the impact of the construction of the Bener dam, the conflict has been ongoing. The governor's permit said that Wadas will be impacted by the construction of the dam. The construction of dam infrastructure brought up the conflict because locals were afraid that it would harm natural ecosystems and sources of livelihood in the area. After the apparatus launched oppressive activities, the disagreement escalated and became a national issue. This prompted NU and Muhammadiyah, the two largest community organizations in Indonesia, to take a stance on the matter. This investigation's objective is to ascertain the Islamic worldview with regard to the preservation of natural habitats and land in the context of wadas. The research method that was employed was looking through books in libraries, and the major data that was used was LBH Yogyakarta's findings from their investigation. The findings of the study lead one to the conclusion that the dispute over property in Wadas is not in line with the Islamic perspective on the importance of preserving the environment. Kasus Wadas mengacu pada sengketa tanah yang timbul antara masyarakat setempat dengan pemerintah di Desa Wadas, Kabupaten Bener, Purworejo, Jawa Tengah, sebagai akibat langsung dari proyek konstruksi skala besar. Sejak 2018, saat izin lingkungan diberikan gubernur yang menyatakan bahwa Wadas masuk dalam lokasi dampak pembangunan bendungan Bener, konflik terus berlangsung. Di dalam izin yang dikeluarkan oleh Gubernur Jawa Tengah Ganjar Pranowo menyebutkan, Wadas akan terkena dampak pembangunan bendungan tersebut. Pembangunan infrastruktur bendungan memunculkan konflik karena warga khawatir akan merusak ekosistem alam dan sumber penghidupan di daerah tersebut. Setelah aparat melancarkan aktivitas penindasan, ketidaksepakatan meningkat dan menjadi isu nasional. Hal itu mendorong NU dan Muhammadiyah, dua ormas terbesar di Indonesia, mengambil sikap soal itu. Tujuan investigasi ini adalah untuk mengetahui pandangan Islam tentang pelestarian habitat alam dan lahan dalam konteks wadas. Metode penelitian yang digunakan adalah mencari melalui buku-buku di perpustakaan, dan data utama yang digunakan adalah temuan-temuan LBH Yogyakarta dari penyelidikan mereka. Temuan penelitian ini membawa pada kesimpulan bahwa sengketa harta benda di Wadas tidak sejalan dengan perspektif Islam tentang pentingnya menjaga kelestarian lingkungan.